Ephedrine induced psychotic disorder: case report - Gülpek, Demet; Coşkunol, Hakan; Kesebir, Sermin (Journal of Dependence, 2002)
There has been many cases of “Ephedrine abuse and psychotic disorders related to ephedrine dependence” in foreign medical literature. In this article “Ephedrine dependence and ephedrine-induced psychotic disorder” is reviewed with a case. The case was using ephedrine for 25 years and in the last 4 years he had auditory hallucinations. He had attempted to give up the drug for many times but he could not achivie. The case was treated in the Addictive Disorders inpatient unit of department of psychiatry. Ten days after hospitalisation, patient’s auditory hallucinations were dissapered without any antipsychotic medication.
Keywords: Ephedrine; ephedrine dependence; psychotic disorder